Educational Level Differences in Knowledge and Perceptions of Sugar-Sweetened Beverages in Central Semarang - Oktia Woro Kasmini Handayani; Irwan Budiono; Puput Ediyarsari; Vilda Ana Veria Setyawati; Eti Rimawati; Syifa Nasir; Denilay Richardo Rambing (Jurnal Kesehatan Masyarakat, 2026)
Indonesia is ranked third with the highest level of Sugar-Sweetened Beverages (SSB) consumption in Southeast Asia in 2020. SSB consumption is one of the factors in the increase in cases of Diabetes Mellitus (DM) in society, especially in children. Research purposes is to get an overview of knowledge and perceptions related to SSB consumption at various levels of education (elementary school, middle school, high school and university students). A quantitative method was used with a target population of 19,880 students across elementary, middle, high schools, and universities in Central Semarang. Proportional stratified random sampling yielded a sample size of 376 participants using the Isaac and Michael formula. The study used an SSB knowledge and perception questionnaire along with FGD guidelines. Chi-square and ANOVA tests revealed that knowledge and perceptions significantly influence SSB consumption across education levels (F: 28.053, sig 0.000), indicating that greater awareness could encourage healthier choices. The lack of knowledge about SSB consumption was most evident among elementary school children, with 72.19% reporting excessive intake. Negative perceptions were primarily found among students, followed by 56.16% in the student group, 43.48% in junior high, and 18.39% in high school. In conclusion, our study contributes to the understanding of the knowledge and perceptions in this research together have a significant influence on SSB consumption at various levels of education. This research provides insights into the importance of nutritional awareness at an earlier stage of education. Future studies should address the education intervention od SSB consumption in children.